Practice-Centered HCI: Teaching in Undergraduate Computing Courses in Brazil - Guimarães, Tatiane Gomes; Prates, Raquel Oliveira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Human-Computer Interaction is a multidisciplinary field that is taught in Computing undergraduate courses. Although HCI Education has been a theme for research both nationally and internationally, much of this existing research is focused on syllabi guidelines and the topics being taught.We propose an in-depth research so we can better understand how HCI is being taught in Computing undergraduate courses in Brazil. For that, we chose to use the UDUM method, conducting semi-structured interviews with thirteen geographically distributed HCI professors that teach introductory courses in Computing departments and courses in Brazil. Among our results, an aspect that stood out was the high value given to practice by our interviewees, which is the focus of this paper. The interviewees value conducting the course itself guided by a life cycle in HCI, walking through different phases and teaching respective methods and techniques in a practical way, where students can exercise and practice what they are learning in hands-on projects during the course.